A Comparative Study of the Innate Humoral Immune Response to Avian Influenza Virus in Wild and Domestic Mallards - van Dijk, Jacintha G. B.; Verhagen, Josanne H.; Hegemann, Arne; Tolf, Conny; Olofsson, Jenny; Järhult, Josef D.; Waldenström, Jonas (Frontiers in Microbiology, 2020)
Domestic mallards (Anas platyrhynchos domesticus) are traditionally used as a model to investigate the immune response to low pathogenic avian influenza virus (LPAIV) in free-living mallards. However, it is unclear whether the immune response of domestic birds reflect the response of their free-living counterparts naturally exposed to this virus. We investigated the extent to which the innate immune response was similar among (i) wild-type domestic mallards in primary and secondary infection with LPAIV H4N6 in a laboratory setting (laboratory mallards), (ii) wild-type domestic mallards naturally exposed to LPAIV in a semi-natural setting (sentinel mallards), and (iii) free-living mallards naturally exposed to LPAIV. We quantified innate immune function by measuring non-specific natural antibodies, complement activity and the acute phase protein haptoglobin. We demonstrate that complement activity in the first three days after LPAIV exposure was higher in primary-exposed laboratory mallards than in sentinel and free-living mallards. LPAIV H4N6 likely activated the complement system and the acute phase response in primary-exposed laboratory mallards, as lysis was higher and haptoglobin lower at day 3 and 7 post-exposure compared to baseline immune function measured prior to exposure. There were no differences observed in natural antibody and haptoglobin concentrations among laboratory, sentinel and free-living mallards in the first three days after LPAIV exposure. Our study demonstrates that domestic mallards seem an appropriate model to investigate innate immunology of their free-living counterparts, albeit the innate immune response of secondary-LPAIV exposed mallards is a better proxy for the innate immune response in pre-exposed free-living mallards than that of immunologically naïve mallards.